Classicism vs. Modernism in the Plays of T.S. Eliot: A Rare but Effective Art of Dramatization - ALYAHYA, RIMAH SALEH (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
T.S. Eliot is an exceptional, unusual playwright. He fuses classicism and modernism in his plays and other literary works. However, this rare technique of making plays has been successfully used by him. He combines Greek myth and Christian rituals with contemporary issues, especially those relating to the masses or average citizens, in order to express his cultural ideals. Because of this special technique that is effectively wielded only by a few playwrights, T.S. Eliot included, he became an enigma for many literary historians. This paper thoroughly analyzes how T.S. Eliot uses both classicism and modernism in his plays, which is a rare but effective art of dramatization.